Changing conceptions among regular children using storybooks on special children - Pineda, Gereon Pilipino M. (2006)
This research developed 5 storybooks which featured characters who had autism, Down's syndrome, physical disability, hearing impairment, and visual impairment. The storybooks were read and discussed to GRade 3 children. The research found out that storybooks could be an effective means in changing the conceptions of regular children about special children. Along with other instruments, a conceptions inventory pretest and posttest whose items were culled from the storybooks and were clustered into the areas of independence, learning potential, sociability, use of senses, ability to work, physical ability, and communication were administered to 24 respondents to find out their conceptions about special children. After the storybook reading and discussion, the respondents regarded children with autism, Down syndrome, physical disability, and hearing impairment as individuals who were capable of achieving a level of independence in the course of their everyday life. The respondents likewise regarded children with Down syndrome, physical disability, hearing impairment , and visual impairment as having the potential to learn. they also perceived children with down syndrome, physical disability, and hearing impairment capable of using their senses in tasks that required them to. They also found children with Down Syndrome and those with physical disability sociable. The respondents also regarded children with down syndrome and physical disability as having the potential or ability to work. The respondents likewise thought children with physical disability as being physically able to carry out specific tasks.